2019
DOI: 10.1002/rmv.2078
|View full text |Cite
|
Sign up to set email alerts
|

Emerging hepatitis E virus compared with hepatitis A virus: A new sanitary challenge

Abstract: Summary Hepatitis A (HAV) and E (HEV) viruses are able to cause liver disease in humans. Among the five classical hepatotropic viruses, they are mainly transmitted via the fecal‐oral route. Historically, many similarities have thus been described between them according to their incidence and their pathogenicity, especially in countries with poor sanitary conditions. However, recent advances have provided new insights, and the gap is widening between them. Indeed, while HAV infection incidence tends to decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 142 publications
(196 reference statements)
0
11
0
Order By: Relevance
“…Water is a major vector for transmission of many human enteric viruses (e.g., noroviruses, hepatitis A and E viruses, enteroviruses). Transmission occurs either directly through consumption of drinking water or by swallowing water during recreational activities, or indirectly through consumption of food in contact with polluted water (i.e., lettuce, red fruits, shellfish) (Hirneisen et al, 2010;Blanco et al, 2017;Kauppinen and Miettinen, 2017;Hartard et al, 2019). Most enteric viruses are small particles (20-40 nm) composed of single-stranded RNA protected inside a capsid made of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Water is a major vector for transmission of many human enteric viruses (e.g., noroviruses, hepatitis A and E viruses, enteroviruses). Transmission occurs either directly through consumption of drinking water or by swallowing water during recreational activities, or indirectly through consumption of food in contact with polluted water (i.e., lettuce, red fruits, shellfish) (Hirneisen et al, 2010;Blanco et al, 2017;Kauppinen and Miettinen, 2017;Hartard et al, 2019). Most enteric viruses are small particles (20-40 nm) composed of single-stranded RNA protected inside a capsid made of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed not only an increased number of hepatitis E cases in recent years but also a high number of severe and/or lethal cases as an emerging source of morbidity and a new healthcare challenge [37]. This increase cannot be explained by better detection as the same protocol was used since before this study started (2016).…”
Section: Discussionmentioning
confidence: 72%
“…Due to its potential for HEV strain genotyping 35 as well as its functional impact, 14,25,36 the ORF2/ORF3 overlapping region was targeted for sequencing. A nested PCR system 35 was performed giving an amplification product of 137 bp (nt 5290-5426).…”
Section: Ultra-deep Sequencing and Molecular Patterns Investigationmentioning
confidence: 99%